2020
DOI: 10.1097/tp.0000000000002913
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Intrapatient Variability, Time in Therapeutic Range, and Risk of De Novo Donor–Specific Antibodies

Abstract: Background. Tacrolimus (TAC) is the most important agent for maintenance immunosuppression and prevention of immunologic injury to the renal allograft, yet there remains no consensus on how best to monitor drug therapy. Both high TAC intrapatient variability and low TAC time in therapeutic range (TTR) have been associated with risk of de novo donor–specific antibodies (dnDSA). In this study, we hypothesized that the risk associated with high TAC coefficient of variation (CV) is a result of low TAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 22 publications
3
54
1
Order By: Relevance
“…Among patients with high CV, those with low TTR had significantly higher risk for dnDSA, acute rejection, and death‐censored graft loss compared with high TTR. Among patients with high TTR, outcomes were not significantly different when comparing those with low and high CV 61 . These results suggest combining IPV measures may offer stronger predictive value, however, further studies in this area are necessary.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Among patients with high CV, those with low TTR had significantly higher risk for dnDSA, acute rejection, and death‐censored graft loss compared with high TTR. Among patients with high TTR, outcomes were not significantly different when comparing those with low and high CV 61 . These results suggest combining IPV measures may offer stronger predictive value, however, further studies in this area are necessary.…”
Section: Resultsmentioning
confidence: 77%
“…A recent study in adult kidney transplant recipients also identified an association between TTR less than 78% and risk of rejection, graft loss, mortality, and infection 59 . Davis et al conducted two analyses within a single group of adult kidney transplant recipients utilizing TTR and CV 60,61 . The first analysis used a cutoff of TTR less than 60% to identify high‐risk patients based on warfarin literature.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies have further investigated the role that high Tac IPV plays in dnDSA development. Davis et al reported that immunologic risk associated with high Tac IPV can be attributed to time spent outside of therapeutic range 20 . Using mean Tac IPV alone may overlook individuals at higher immunologic risk.…”
Section: Impact Of Tac Ipv On Clinical Outcomesmentioning
confidence: 99%
“…In a subsequent evaluation by the same study group, it was reported that patients with CV% >44.2% and TTR <40% had an increased risk of dnDSA (OR, 4.93; 95% CI, 2.02-12.06; P < 0.001). 16 Additionally, patients with CV% >44.2% and TTR <40% had an increased association with death-censored graft loss at 5 years (HR, 4.00; 95% CI, 1.31-12.24; P = 0.015). This study identified their CV% and TTR thresholds based on ROC curve analysis.…”
Section: Discussionmentioning
confidence: 92%
“…This study identified their CV% and TTR thresholds based on ROC curve analysis. 16 However, this study cohort also included both kidney and pancreas transplant recipients with various tacrolimus off-protocol trough goals, which increased the potential for lower TTR compared with a more homogenous immunosuppression cohort.…”
Section: Discussionmentioning
confidence: 99%